Well-being in crisis: Mindful practices for Canadian higher education instructors (Journal of Applied Learning and Teaching, 2026)
Canadian higher education instructors, particularly non-full-time instructors, are grappling with increasing challenges from precarious employment, chronic underfunding, and inequitable policy shifts. This paper draws on Harney and Moten’s The Undercommons and Thich Nhat Hanh’s mindfulness philosophy to critique the neoliberal transformation of Canadian higher education, which prioritizes profit over intellectual and social values. It explores the exploitative reliance on international students’ financial contributions and the transformative yet disruptive impact of AI on teaching roles, revealing the detrimental effects of these systems on educators’ well-being. By emphasizing the critical link between educators’ mental well-being and systemic change, the paper advocates for mindfulness as a powerful tool to process strong emotions, promote healing, and inspire the creation of alternative spaces for resistance and meaningful reform.